Pengaruh Kepemimpinan, Disiplin Kerja, dan Komunikasi terhadap Kinerja Karyawan PT. PBI - Susilo, Ridwan; Purbasari, RR Niken (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this study is to identify and analyze the influence of leadership, work discipline, communication as independent variables on the performance of employees of the resin work unit production section at PT. PBI. The form of research in this study is descriptive statistics and causality with multiple regression analysis methods to test hypotheses. The sampling technique used in this study was saturated sampling and used 112 respondents who were permanent employees at PT. PBI, and the data of this study were collected through the distribution of questionnaires using Likert scale. The results of this study show that leadership and work discipline affect employee performance, while communication has no influence on the performance of PT employees. PBI part of resin work unit production. This is possible because the work pattern of employees in the production section of the resin work unit is mechanistic which can eliminate the role of communication. Leadership and discipline factors for companies are important aspects to improve performance.